DOI: 10.4995/thesis/10251/6881
|View full text |Cite
|
Sign up to set email alerts
|

Cost Efficient Provisioning of Mass Mobile Multimedia Services in Hybrid Cellular and Broadcasting Systems

Abstract: One of the challenges that the wireless industry faces today is to provide mass multimedia services to mobile and portable devices at low cost, making them affordable to users and profitable to operators. The most representative service is mobile TV, which is expected to become a key application in future wireless networks. Nowadays cellular networks cannot support large scale consumption of such services, and newly deployed mobile broadcasting networks are very expensive to deploy due to the large investment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 92 publications
(143 reference statements)
0
9
0
Order By: Relevance
“…The results obtained in field tests [44,45] have revealed that the use of TI at the physical layer outperforms MPE-iFEC in every reception scenario. Although long TI achieves the largest gain in LMS channels, it has been shown to achieve significant gains in terrestrial channels as well [10,46,47]. In particular, the utilization of Application Layer -Forward Error Correction (AL-FEC) has been proposed for extending the protection of DVB-H services across multiple time-slicing bursts.…”
Section: Time Diversity In Mobile Broadcasting Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results obtained in field tests [44,45] have revealed that the use of TI at the physical layer outperforms MPE-iFEC in every reception scenario. Although long TI achieves the largest gain in LMS channels, it has been shown to achieve significant gains in terrestrial channels as well [10,46,47]. In particular, the utilization of Application Layer -Forward Error Correction (AL-FEC) has been proposed for extending the protection of DVB-H services across multiple time-slicing bursts.…”
Section: Time Diversity In Mobile Broadcasting Systemsmentioning
confidence: 99%
“…As a result, the costs associated to the deployment of mobile broadcasting networks with good coverage are only justificable in urban areas with a high user density, where it is possible to eventually recover the initial investment in infrastructure. In order to avoid this situation, it would be desirable to perform an incremental deployment that follows the user demand [10]. Within this scenario, the cellular network would prevent the over-dimensioning of the broadcasting capacity, and would ensure the service continuity in low populated areas with no initial broadcasting infrastructure.…”
Section: 1 Evolution Of Terrestrial Mobile Broadcasting Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also supports the concept of Rotated Constellations (RC) and includes an additional 256QAM constellation. Standardization activities were also addressed on the development of mobile broadcasting systems, despite the lack of market and financing needed [13]. The handheld evolution of DVB-T2, Digital Video Broadcasting -Next Generation Handheld (DVB-NGH), is the state-of-the-art standard for DTT mobile communications, and includes some of the most advanced transmission techniques to cope with adversities and characteristics of mobile channels [14].…”
Section: Next-generation Digital Terrestrial Broadcastingmentioning
confidence: 99%